2011
DOI: 10.1186/1471-2474-12-251
|View full text |Cite
|
Sign up to set email alerts
|

Asian-Specific total knee system: 5-14 year follow-up study

Abstract: BackgroundKnee size and body size differ in Asians compared with Caucasians. Nevertheless, many total knee arthroplasty (TKA) prostheses used worldwide are made for Western Caucasian subjects. As a result, an Asian's knee might not fit these prostheses. We studied the Flexible Nichidai Knee (FNK) system, a new model of TKA for Asian patients. The purpose of this report is to investigate the outcomes of this prosthesis retrospectively.MethodsWe investigated 1055 primary TKAs in 595 patients who underwent FNK fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
(20 reference statements)
3
16
0
1
Order By: Relevance
“…Finally, the contact area and stress force of the post-cam was not directly evaluated in our study. Nevertheless, the current study theoretically supports the previously reported clinical outcomes of the FNK PS-TKA, with a good range of motion and recovery of the postoperative quadriceps and hamstring power [5,6].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, the contact area and stress force of the post-cam was not directly evaluated in our study. Nevertheless, the current study theoretically supports the previously reported clinical outcomes of the FNK PS-TKA, with a good range of motion and recovery of the postoperative quadriceps and hamstring power [5,6].…”
Section: Discussionsupporting
confidence: 90%
“…1). It constrains the valgus-varus motion within ±2°at 0°and ± 4°at 90°of flexion, and the internal-external rotation within ±6°at 90°of knee flexion [5]. Table 1 compares the features of axial rotation and varus-valgus constraint of FNK, with other PS, CCK, and semi-constrained TKA systems.…”
Section: Prosthesis Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TKA is considered a highly successful procedure, with the ability to relieve pain, enhance quality of life, and improve function in patients with knee arthritis [11], nearly all TKA prostheses were designed based on the anthropomorphic features of male [49], Western, and primarily white patients [6, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…In the long run, surgeons speculate a lower occurrence of intra-operative and post-operative fractures too. Multiple authors [20,21,22,23,24] have also shown that the the most common problem in implants is with respect to the length and the modified implant tends to perform better in the Asian population compared to their original counterpart. Hence, this highlights the need to modify the humeral implants too.…”
Section: A Related Workmentioning
confidence: 99%